Optimasi Kinerja Seismik Sambungan Struktur untuk Aplikasi Rekayasa Teknik Sipil - Budi Suswanto; Cintantya Budi Casita; Chien-Kuo Chiu; Triwulan Triwulan; Hidayat Soegihardjo Masiran; Heppy Kristijanto; Data Iranata (MEDIA KOMUNIKASI TEKNIK SIPIL, 2025)
This study evaluates the seismic performance of steel moment-resisting frames through the integration of reduced beam sections (RBS) with externally reinforced cover plates. Three-dimensional finite element analyses under cyclic loading were conducted to assess the influence of cover plates on different RBS geometries, including radius cut (RBSCP-RC), straight cut (RBSCP-SC), tapered cut (RBSCP-TC), and drilled flange (RBSCP-DF). The objective of this study is to investigate the effects of geometric variation on seismic response, moment capacity, and ductility of hybrid RBS–cover plate (RBSCP) connections. The novelty of this research lies in the systematic development and evaluation of a hybrid RBS–cover plate connection that combines the energy dissipation capability of RBS with the strengthening function of cover plates. This configuration is intended to shift plastic hinge formation away from the column face, reduce the risk of premature weld failure, and improve connection strength and energy dissipation. The numerical results indicate that the incorporation of cover plates significantly enhances the seismic performance of RBS connections, with the radius-cut configuration demonstrating the most stable hysteretic behavior and the highest energy dissipation capacity. These findings emphasize the importance of geometric optimization in hybrid RBS–cover plate designs and provide valuable guidance for improving the seismic resilience of steel moment-resisting frames.